The Use of Bessel Light Beams for the Photothermal Probing of Heterogeneous Media. - Astakhov, П. В.; Mityurich, Георгий Семенович (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
The work is devoted to the research of thermophysical properties spatially heterogeneous media by the photodeflection spectroscopy method with the excitation of the sample by laser Bessel beam.